Research on the cultivation of college students’ innovative ability by industry-teaching integration model based on personalized education - Ru Chen; Wang Qun (ITM Web of Conferences)
In the era of vigorous development of higher education, the cultivation of college students' innovation ability has become a core issue. This paper explores the role of industry-teaching fusion mode based on personalized education in the cultivation of college students' innovative ability. The industry-teaching fusion mode based on personalized education can carefully formulate personalized cultivation programs based on students' individual differences and deeply integrate the actual needs of the industry into all aspects of education and teaching. This model can significantly enhance the innovative consciousness and practical ability of college students and promote the cultivation of innovative thinking. Students are practiced in real industrial environments such as enterprise practice and project cooperation, effectively improving their comprehensive quality. This study not only provides new ideas for the reform of higher education, but also lays a solid foundation for the cultivation of innovative talents in line with the needs of society, which has important theoretical and practical value.